MODEL MENGAJAR DALAM PEMBELAJARAN: ALAM SEKITAR, SEKOLAH KERJA, INDIVIDUAL, DAN KLASIKAL - Muhammad Idris Usman (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2012)
Essentially, instruction is an activity that is carried out by educators in a programmed way so that learners are able to learn actively. Instructional process is implemented to develop learners’ creativity. Problems faced by educators in teaching and learning process still revolves around the use of traditional methods that have already gone. The teaching and learning process still places the learner as an object of study, whereas, it should be based on learner-centered. To overcome the problems faced in the instructional process, there are several instructional models, environmental learning model, school learning, individual, and classical learning models. Those instructional models can be applied essentially according to the situation, condition, and material taught in the instructional process.